Analysis of cashiers’ work postures using the Quick Exposure Check (QEC): a case study in Yogyakarta - Prahasti, Saptiana Nur; Vicananda, Ladayan Pradana; Ma’ruf, Khakam; Setiawan, Rizal Justian; Azizah, Nur (Operations Excellence: Journal of Applied Industrial Engineering, 2023)
The analysis of cashiers' work postures aims to minimize or avoid musculoskeletal problems. The research uses Quick Exposure Check (QEC) to identify working condition problems that focus on the back, shoulders, arms, and neck. The goal is to improve working conditions by reducing the risk of worker fatigue, unergonomic work postures, and musculoskeletal pain, which leads to increased productivity. To determine the extent of musculoskeletal disorders, the research method uses a quick exposure check that focuses on the upper body, including the back, neck, arms/shoulders, and wrists, which are common problem areas for workers. Based on the collected data, the exposure score and level are calculated to determine the follow-up to the research. The data shows that 50% of cashiers have an exposure level of 50 - 60%, and further research and changes are required. Meanwhile, another 50% of cashiers have an exposure level value above 70%, requiring immediate research and changes. The conclusion of this analysis is that it is essential to continuously check and maintain the ergonomics of the cashier's work. Regular inspections and necessary corrective actions must be conducted to ensure ergonomic working conditions and protect the health of cashiers.